OBSTACLE-AVOIDING ROBOTICS: THEORETICAL FRAMEWORK AND SENSOR-BASED NAVIGATION - Raximov Habibulloh (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2025)
Obstacle avoidance represents one of the most essential functions required for autonomous mobile robots, allowing them to navigate safely through dynamic or unknown environments. This theoretical study explores the design principles and operational mechanisms behind ultrasonic sensor–based obstacle-avoiding robotics. The paper examines the fundamentals of ultrasonic sensing, microcontroller integration, motion control algorithms, and system architecture. The proposed model emphasizes a low-cost and scalable approach that can be applied in educational laboratories, beginner robotics programs, and prototype development. Although the study remains conceptual, the presented framework closely reflects real-world robotic systems and can be directly adapted for practical implementation. The findings demonstrate that ultrasonic-based navigation remains an accessible, affordable, and reliable method for early-stage robotic development, providing a strong foundation for more advanced applications such as AI-assisted navigation, SLAM systems, and multi-sensor fusion robotics.